2017
DOI: 10.1111/jce.13143
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Undersensing by a Noise Detection Algorithm That Utilizes Far‐Field Electrograms With Near‐Field Bandpass Filtering

Abstract: The SecureSense algorithm can withhold appropriate therapies for ventricular arrhythmias due to design and programming limitations. Electrophysiologists should have a thorough understanding of the SecureSense algorithm before routinely programming it and understand the implications for ventricular arrhythmia misclassification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Alternatively, one may consider reducing the range of the Wavelet EGM source to improve the signal resolution. Above all, this raises the question of the need to test systematically the FF detection at implant, as suggested by others to improve the accuracy of noise detection algorithms that rely on this EGM source 11 . Regarding the question of optimizing the % match threshold, our results indicate that the Abbott and Medtronic nominal thresholds are similar or close to the optimal calculated thresholds.…”
Section: Discussionsupporting
confidence: 51%
“…Alternatively, one may consider reducing the range of the Wavelet EGM source to improve the signal resolution. Above all, this raises the question of the need to test systematically the FF detection at implant, as suggested by others to improve the accuracy of noise detection algorithms that rely on this EGM source 11 . Regarding the question of optimizing the % match threshold, our results indicate that the Abbott and Medtronic nominal thresholds are similar or close to the optimal calculated thresholds.…”
Section: Discussionsupporting
confidence: 51%
“…As a result, neither the Medtronic Lead Noise Detection ™ nor the Abbott “ RV lead noise ” alert were reached. This is important since these alerts may inhibit therapy, a feature that can have adverse consequences …”
Section: Discussionmentioning
confidence: 99%
“…As such, programming guidelines recommends faster detection rate cutoffs and longer detection times to reduce avoidable HV therapy. However, multiple reports have revealed that generic compliance with guideline directed ICD programming recommendations, with or without undersensing, may lead to delayed or in some instances even withholding delivery of the HV therapy [13][14][15]23 . Moreover, post-mortem studies suggest that mortality in ICD implanted patients can be due to undertreated ventricular tachyarrhythmias 13,18,24,25 .…”
Section: Discussionmentioning
confidence: 99%